Revisiting the Material Development of The Quran: A Quranic Study of Keith E. Small's Book of Divine Encounter - Fitri, Annisa; Shidqon, Alfan; Rahmati Nuzuliyah, Wilda (AN NUR: Jurnal Studi Islam, 2023)
Throughout history, the Quran underwent physical transformations that reflected the development of society and technology. The book "Qurans: Books of Divine Encounter" by Keith E. Small presents a visual history of the Quran through 55 rare manuscripts from parchment to paper in the Bodlein collection from around the world. These manuscripts were acquired through purchase, but also existed as inheritances, adventurers, scholars, diplomats, clerics, and from royalty. This book is not just a collection of images but a visual guide that reveals the evolution of Quranic writing over time. This study is a revisiting of the book, focusing on the development of Quranic materials from parchment to paper. The research method begins by analyzing the literature and works of Keith E. Small. There are two findings from this paper. First, this book is Keith E Small's attempt to move away from outsider studies that were initially confined to the ontological and epistemological study of the Qur'?n towards a future historical stream, namely the relationship between Qur'?nic visualization and the status of the authenticity of Qur'?nic revelation as seen in the stability of Qur'?nic copies and the preservation of the divine kalam. Secondly, the book highlights the central role of the Qur'?n as an integral pillar in Islamic history, art and culture, as well as the importance of the scripture in shaping Muslim identity and the course of civilization.